2010
DOI: 10.1890/09-2070.1
|View full text |Cite
|
Sign up to set email alerts
|

Community genetic interactions mediate indirect ecological effects between a parasitoid wasp and rhizobacteria

Abstract: Abstract. Indirect ecological effects (IEEs) clearly influence species dynamics and abundance, yet relatively little is known about how they influence the evolution of species involved. While genetic variation in the species causing and responding to the IEE has obvious effects, the influence of genetic variation in intermediate species remains unexamined. Given the often counterintuitive responses of populations to IEEs this seems a significant omission. Following a community genetics approach, we used a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…These results are consistent with community genetics results from other systems (e.g. [4,7,8,[77][78][79]). However, our unique experimental manipulations involving genotypic diversity in multiple coexisting species have exposed novel direct genetic effects that influence species abundance, and potential feedbacks between these effects and genotypic composition in other species in the community.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with community genetics results from other systems (e.g. [4,7,8,[77][78][79]). However, our unique experimental manipulations involving genotypic diversity in multiple coexisting species have exposed novel direct genetic effects that influence species abundance, and potential feedbacks between these effects and genotypic composition in other species in the community.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that simultaneously manipulate the genetic composition of multiple species and other environmental attributes will be a necessary first step towards understanding the importance of G Â G Â E interactions on demography and community structure (e.g. [55,56]). …”
Section: What Is the Relative Importance Of Intraspecific Genetic Varmentioning
confidence: 99%
“…This has been shown to occur by active choice (host preference) of the aphid and to a small extent, through effects on reproductive performance. Our results indicate that aphid choice behavior could lead to assortative associations of aphid genotypes and barley genotypes, and the influence of these genetically-based interactions between aphid and plant could have evolutionary effects for the rest of the interacting community (Astles et al 2005;Bukovinszky et al 2008;Zytynska et al 2010). However, the use of even a single host genotype by all aphid genotypes, such as BCD47 in this study, could decrease the effect on higher trophic organisms.…”
Section: Discussionmentioning
confidence: 82%
“…Previous work has demonstrated that genetically based interactions between species can influence the phenotypes of both the directly and indirectly interacting individuals (Service 1984;Carius et al 2001;Tétard-Jones et al 2007;Zytynska et al 2010). For example, the indirect effect of a soil rhizobacteria on the body-size (fitness) of a parasitoid wasp was mediated by genotypic interactions between the linking barley and aphid species (Zytynska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation